Doctor, can I desensitize my food-allergic child using directly the allergenic molecules?. Issue 3 (June 2016) - Buonomo, Alessandro; Nucera, Eleonora; Schiavino, Domenico
Abstract : Purpose of review: Food allergy has risen in prevalence worldwide and is one of the main causes of anaphylaxis, especially in children. The only possible therapeutic approach is specific immunotherapy. This review describes the recent approaches using allergenic molecules for specific immunotherapy. Recent findings: Hypoallergenic tropomyosins from Metapenaeus ensis have been cloned and constructed by direct mutagenesis or epitope deletion and have been successfully used in shrimp-sensitized mice. A modified carp parvalbumin is being used in phase I/IIa clinical trials in patients with fish allergy. Natural lipid transfer protein (Pru p 3) and profilin (Pho d 2) extracts have been used for the treatment of patients with plant food allergy. Treatments of egg-sensitized mice with glycated-ovalbumin and ovomucoid peptides led to a clinical and immunological improvement. A preventive treatment with synthetic β-lactoglobulin peptides was effective in reducing skin symptoms in mice sensitized to milk whey proteins but no dominant epitopes were found in α-lactalbumin. Finally peanut desensitization has been attempted using three modified recombinant peanuts but the protocol was interrupted and limited to a phase 1 study because of side-effects. Summary: Many molecules, including allergenic peptides or modified proteins are under consideration but clinical trials in food-allergic study participants are necessary to confirm tolerability and efficacy.